Language that judges love: A study of illocutions in the lyrics of the song Al-Mahkama by Kazim Al-Saher - Nur Islamiyah; Cahya Buana; Minatur Rokhim; Hafizh Jawd Naufal; Khamesyah Naumi Azzahra (Pusat Studi Bahasa dan Publikasi Ilmiah, 2026)
This study aims to explain the use of illocutionary acts in the lyrics of the song Al-Mahkama performed by Kazim Al-Saher and Asma El Mnawar, which describes a dialogue of a couple of lovers who demand justice for their broken love relationship. The title Al-Mahkama is not merely a metaphor, but rather the main concept that forms the structure of the dialogue in the song, where love is seen as a matter to be judged, and language functions as a tool to assess, demand, and declare the truth. This study aims to identify the types and communicative functions of the illocutionary acts contained in the lyrics of the song. This research uses a qualitative descriptive method with song lyrics as primary data, while the analysis is based on Searle’s speech theory. The result of the research show that there are three types of illocution speech that are dominantly used, namely assertive (as statements and defenses), directive (as orders and requests for justice), and expressive (as emotional expressions). These three findings represent a concrete manifestation of language that judges love, where every utterance functions as a judicial process. Language used not only to express feelings but also to judge, demand justice, and establish truth from each speaker's perspective. This research contributes to the development of pragmatic studies and expands linguistic research in the field of modern Arabic music.